2013
DOI: 10.1134/s1063778813100074
|View full text |Cite
|
Sign up to set email alerts
|

Coherent dissociation of relativistic 12N nuclei

Abstract: The dissociation of relativistic 12 N nuclei having a momentum of 2 GeV/c per nucleon and undergoing the most peripheral interactions in a track emulsion is studied. The picture of charged topology of product ensembles of relativistic fragments and special features of their angular distributions are presented. DOI: 10.1134/S1063778813100074The track-emulsion method has still retained its exceptional position as a means for studying the structure of fragmentation of relativistic nuclei owing to the completeness… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Contribution of the unstable nuclei 6 Be, 8 Be and 9 B into dissociation of relativistic nuclei 7,9 Be, 10 B and 10,11 C is under study on the basis of the nuclear track emulsion exposed to secondary beams of the JINR Nuclotron.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contribution of the unstable nuclei 6 Be, 8 Be and 9 B into dissociation of relativistic nuclei 7,9 Be, 10 B and 10,11 C is under study on the basis of the nuclear track emulsion exposed to secondary beams of the JINR Nuclotron.…”
Section: Discussionmentioning
confidence: 99%
“…The feature of 7 Be dissociation is an approximate equality of probability of the main channels 2He and He + 2H of coherent dissociation (Table I). Their ratio is equal to 0.7 ± 0.1 [11]. Recently obtained statistics of 140 10 B "white" stars is presented in The unstable nuclei in dissociation of the 9 Be, 10 Earlier, basing on the Q αp energy distribution of the triples 2α + p from the "white" stars 10 C → 2α + 2p it is concluded that in the 10 C nucleus the core 9 B is manifested with a probability of 30 ± 4%, and the 8 Be g.s.…”
Section: Nuclear Clustering In Relativistic Dissociationmentioning
confidence: 95%
See 1 more Smart Citation
“…From the experimental point of view, the last channel is a three-body one and can involve the decays of both the ground state (0 + ) of the 8 Be nucleus and its 2 + excited state. Moreover, channels that, in charge topology, correspond to the dissociation of the 7 Be and 10 B core nuclei should appear. Thereby, one expects that the role of multi-particle channels in the coherent cluster dissociation of 11 C nuclei should be significant, so that the application of the nuclear-track-emulsion method is reasonable.…”
Section: Potential Of the Nuclear-emulsion Methodsmentioning
confidence: 99%
“…The decay of the 11 C nucleus leads to the formation of the stable isotope 11 B, which one can observe in cosmic rays. This scenario of nucleosynthesis is not commonly recognized-the isotopes 10,11 B are assumed to be products of the bombardment of carbon-star surfaces with high-energy protons. If observations reveal the dissociation of 11 C nuclei through the 7 Be + α and 3 He + 8 Be channels, this would confirm the existence of cluster modes in this nucleus that are genetically related to its synthesis.…”
mentioning
confidence: 99%